Evaluation of learning environments for object-oriented programming: measuring cognitive load with a novel measurement technique - Uysal, Murat Pasa (Interactive learning environments, 2016)
Various methods and tools have been proposed to overcome the learning obstacles for Object-Oriented Programming (OOP). However, it remains difficult especially for novice learners. The problem may be not only adopting an instructional method, but also an Integrated Development Environment (IDE). Learners employ IDEs as a means to solve programming problems and an inappropriate IDE may impose additional cognitive load. Therefore, this quasi-experimental study tried to identify the cognitive effects of a more visually supportive and functional IDE. It was explored by the functional near-infrared spectroscopy method, which is a relatively new physiological tool for measuring cognitive load. Novice students participated in the study in two experimental groups and they were required to write a Java application using two different IDEs. The results indicated a significant difference between the experimental groups and the findings are discussed in view of the principles of Cognitive Load Theory and Multimedia Learning.